The Behavioural Intention to Adopt E-Banking Services Among Small and Medium Sized Enterprises in Mogadishu-Somalia - Ahmed, Sara Hussein (2023)
This thesis studies the variables that impact SMEs' use of e-banking services in Mogadishu, Somalia. The purpose of this study is to identify the primary drivers and challenges affecting the adoption of e-banking services by small and medium-sized enterprises (SMEs), and to provide suggestions for improving the adoption process. The research collects data on SME owners' and managers' attitudes and experiences with e-banking services using a survey and interviews. The results of the research reveal that effort expectance, performance expectance, social influence and facilitating conditions have a positive influence to the adoption of e-banking services among small and medium-sized enterprises (SMEs) in Mogadishu. On the basis of these findings, alluring, and informative actions should be undertaken to increase users' understanding of these benefits, and e-banking services should be created in such a way that customers encounter no issues while utilising them. It is advised that all SMEs in Mogadishu, Somalia, be given access to the infrastructure needed in this field, such as high-speed and reasonably priced internet, in order to maximise the beneficial and significant effects of facilitating conditions on adopting e-banking services. This research offers insights for governments and financial organisations attempting to encourage the use of e-banking services in Somalia and other comparable environments.